Performance Evaluation of Malaysian Unit Trusts Using the Modified Sharpe Ratio - Gasim, Sahar Azhari (2008)
Recent studies on mutual funds have stated that the Sharpe ratio is an inappropriate performance measure as it penalizes upside and downside risk equally and assumes that return series are normally distributed which is rarely the case especially in emerging markets such as Malaysia. To mitigate the flaws of the Sharpe ratio it has been proposed to use Value at Risk (VaR) as the risk metric. When normal VaR (VaRN) is used which only penalizes for downside risk the resulting ratio is known as the adjusted Sharpe ratio (ASRN). However, this ratio still assumes that returns are normally distributed. Consequently, to account for the non normality of mutual fund returns the modified VaR (MSRN) which accounts for both skewness and heavy tails is used and the resulting ratio is known as the modified Sharpe ratio (MSRG). Nevertheless, studies on Malaysian mutual fund performance have continued to use the Sharpe ratio as a measure of mutual fund performance and non have used the ASR or MSR. To fill this gap this study aims to analyse the performance of Malaysian mutual funds using MSR. We also analyse fund performance using SR and ASR to see whether these different performance measures produce different rankings. Hence, employing the daily NAV of 24 Malaysian mutual funds from 1998 to 2007 and using the KLCI as the benchmark we first estimate the VaRN, and the VaRG at the 95% and 99% confidence levels. Consequently we compute the SR, ASRN and MSRG. We find that the VaRN underestimates the risk exposure and consequently the ASRN overestimates performance when compared to the VaRG and the MSRG respectively. Nonetheless the ASRN and the MSRG produced the same rankings. Furthermore the SR produced the same rankings as the ASRN and the MSRG for 16 out of the 24 mutual funds analysed in this study. As for the eight funds that experienced a rank change the change was slight. Hence we come to the conclusion that the Sharpe ratio is adequate for purposes of ranking mutual funds.